2013
DOI: 10.1353/hpu.2013.0032
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of Critical Danger Signs of Pregnancy and Delivery, Preparations for Delivery, and Utilization of Skilled Birth Attendants in Nigeria

Abstract: Maternal mortality in northern Nigeria is among the highest in the world. To understand better the pathways through which the socio-demographic environment affects awareness of obstetric danger signs (i.e., potential problems associated with pregnancy), preparations for delivery, and skilled birth attendance, we conducted a survey of 5,083 women with recent pregnancies in three northern Nigerian states. Only 25% attended antenatal care (ANC), and 91% of all births took place at home. Less than one-third knew t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
35
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 21 publications
4
35
6
Order By: Relevance
“…Having ANC follow up for the last recent pregnancy increased the likelihood of good awareness on Obstetric danger signs by 4.28 folds, 5.72 folds and 6.41 folds during pregnancy, delivery and after delivery respectively. Similarly, different study reported ANC attendance increases mothers' awareness of obstetric danger signs [28,29]. In addition having four or more ANC visit increases the odds of mothers' awareness on obstetric danger signs.…”
Section: Discussionmentioning
confidence: 99%
“…Having ANC follow up for the last recent pregnancy increased the likelihood of good awareness on Obstetric danger signs by 4.28 folds, 5.72 folds and 6.41 folds during pregnancy, delivery and after delivery respectively. Similarly, different study reported ANC attendance increases mothers' awareness of obstetric danger signs [28,29]. In addition having four or more ANC visit increases the odds of mothers' awareness on obstetric danger signs.…”
Section: Discussionmentioning
confidence: 99%
“…Although bleeding was the most frequently mentioned sign, less than 10% of women had identified potential blood donors/blood bank services or a facility where they could readily receive emergency obstetric care. In northern Nigeria, [6] Ethiopia [8] and Uganda [9] researchers also found that a significant proportion of rural women did not have adequate knowledge of signs that may signal complications and the majority of pregnant women failed to take the aforementioned BPACR actions. This suggests that many pregnant women may not understand the implications or severity of these symptoms, should they occur, or the extent to which they need to make advance preparations to avoid delays that may arise if they need special care during pregnancy and delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Data from this study also suggest that BPACR practices in Anegbette were remarkably better than those observed among rural women in northern Nigeria, where less than 2.5% of those surveyed had made any provision for a trip to the health facility, saved money or made transport arrangements, compared with at least 34.3% of women in this study. [6] BPACR practices have also been documented to be poor among rural women in Ethiopia [8] and Tanzania. [10] Poor BPACR has the potential to negatively influence the maternal and child health outcomes, as women who are not well prepared are less likely to utilise skilled birth attendants at delivery or respond to complications in an appropriate or timely manner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For 2.2% of respondents, ANC was not important during pregnancy and another 8.7% were not sure of the importance of ANC. Women who did not attend ANC were significantly less likely to be aware of both critical and non-critical pregnancy complications when compared with those who do not know any complications (Doctor et al, 2013). Furthermore, antenatal period clearly presents opportunities for reaching pregnant women with a number of interventions that may be vital to their health and well-being and that of their infants.…”
Section: Discussionmentioning
confidence: 99%